Manajemen Pengawasan Mutu Produk Pada PT. Rolas Nusantara Mandiri Kecamatan Kalibaru Kabupaten Banyuwangi - NURUDIN, AHMAD; SURYAWARDANI, I G A OKA; AGUNG, I DEWA GEDE (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2019)
Management of Product Controlling in PT. Rolas Nusantara Mandiri Kalibaru District Banyuwangi Regency. Quality controlling is an effective and efficient integrated set of activities which are intended to develop, maintain, and improve the quality of several products and services to make consumers satisfied. This current study is aimed at identifying the consumer opinion about the quality of product, the management system of quality controlling, and the costs needed for it. The study was conducted at AMdK 220 ML Merk AirRolas. The data were analyzed using the control map, cost analysis and descriptive qualitative. The data used in the study were the data on the perception of consumers and the number the products produced, the number of damaged products, and the costs needed to support the controlling process from Janary to December 2016. The result of the study showed that the quality of the products were controlled as the proportional value of the damage was between the upper limit and lower limit, showing that the controlling limit value was (p) = 1.3%, the upper controlling limit was (UCL) 2.6%, the lower controlling limit (LCL) was 0%. The costs needed to control the controlling process (QCC) totaled Rp 618, 769,021.19, the costs needed to guarantee the quality was Rp. 5,566,250.00, and the quality costs (TQS) amounted toRp. 674,431,521.9, meaning that the company could compress products by 111,325 glass or 29.9% of the total production. The value of optimum damage (q*) was 371,172.4. 43,33% of the respondents showed highly positive perception, 50% showed positive perception, and 6,67% showed neutral perception.